Analysis of Diversification Strategies in Improving MSMe Performance - Lani Nurhalimah; Nurni Arrina Lestari; Muh. Abdul Aziz (International Journal of Economics, Management and Accounting (IJEMA), 2024)
This research aims to analyze perceived usefulness, social media marketing, and diversification strategies in improving MSME performance. The results of the research show that there is a significant influence between perceived usefulness on diversification strategies, a significant positive influence of perceived usefulness on MSME performance, a significant positive influence of social media marketing on diversification strategies, an insignificant positive influence of social media marketing on MSME performance, and a positive influence diversification strategy has a significant impact on MSME performance. The research method uses quantitative with a purposive sampling technique, for a known population of 254. The sample consists of 108 respondents. Furthermore, the full model SEM test also shows a good model with adequate Goodness Off Fit values. The research results show that the perceived usefulness of social media marketing has a significant positive effect on diversification strategies, which in turn has a significant positive effect on the performance of MSMEs. However, the relationship between social media marketing and MSME performance is not directly significant. This research makes an important contribution in understanding the factors that influence MSME performance through diversification strategies, by considering the role of perceived usefulness and social media marketing.